If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.12x + 0.5(x + -5) = 0.01(2x + -1) Reorder the terms: 0.12x + 0.5(-5 + x) = 0.01(2x + -1) 0.12x + (-5 * 0.5 + x * 0.5) = 0.01(2x + -1) 0.12x + (-2.5 + 0.5x) = 0.01(2x + -1) Reorder the terms: -2.5 + 0.12x + 0.5x = 0.01(2x + -1) Combine like terms: 0.12x + 0.5x = 0.62x -2.5 + 0.62x = 0.01(2x + -1) Reorder the terms: -2.5 + 0.62x = 0.01(-1 + 2x) -2.5 + 0.62x = (-1 * 0.01 + 2x * 0.01) -2.5 + 0.62x = (-0.01 + 0.02x) Solving -2.5 + 0.62x = -0.01 + 0.02x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.02x' to each side of the equation. -2.5 + 0.62x + -0.02x = -0.01 + 0.02x + -0.02x Combine like terms: 0.62x + -0.02x = 0.6x -2.5 + 0.6x = -0.01 + 0.02x + -0.02x Combine like terms: 0.02x + -0.02x = 0.00 -2.5 + 0.6x = -0.01 + 0.00 -2.5 + 0.6x = -0.01 Add '2.5' to each side of the equation. -2.5 + 2.5 + 0.6x = -0.01 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + 0.6x = -0.01 + 2.5 0.6x = -0.01 + 2.5 Combine like terms: -0.01 + 2.5 = 2.49 0.6x = 2.49 Divide each side by '0.6'. x = 4.15 Simplifying x = 4.15
| 9z+15+-2z= | | -3(1+m)=-10-2m | | 8x^3-3x^2+16x-6=0 | | (4x-3)(2x+5)-1=20x-4(2x+1)(2-x)+6 | | 7b-14=3(-2+b) | | 14x+16=-12 | | 6(z-2)=3z-8+3z | | -8n-28=-4(n+1) | | -4n+2n+16=n+7 | | 0.2x=0.1-0.7x | | -3x^3-15x^2-12x=0 | | 3x-14+5x=8x+10 | | 6x=5x+18 | | -8m=1-7m+7 | | -39+6k=5-5(2-8k) | | -39-6x=-3(7x+3) | | 10-7n=-2(5n+7) | | x/6-(-10)=3 | | b-8=36 | | 5x-465=0 | | a*8=b*8-c | | x^2+21x+12=9x+1 | | y=(x+5)2 | | -8(-4+7x)+8x=-17+x | | 10x=300 | | 5(2x+4)=-70 | | -6(9-6x)=10(9+3x) | | 4x^2-11x+15=2x+6 | | 2(a-9)+10=2-(10-10a) | | 2x^3+56x^2+54x=0 | | 2w+21=6w-7 | | -7(a-5)=-8a+29 |